Strategies for sustainable development of the UNESCO Creative Cities: conclusions from the XI UCCN Annual Meeting (2017) - Alves, Pedro (2020)
In 2017, the XI UNESCO Creative Cities Network (UCCN) Annual Meeting took place in Enghien-les-Bains (France), gathering representatives from the 116 Creative Cities and UNESCO. This meeting was an opportunity to present and discuss strategic contributions to several local urban implementations of the 2030 Agenda for Sustainable Development and the New Urban Agenda. It was also an opportunity to raise awareness and to evaluate specific creative strategies being undertaken by each city and each creative field groups, as well as struggles, needs and opportunities for improvement. The event was divided in several sessions, such as the Steering Group working session, the Creative Cities workshops, the Mayors’ Forum or the final Plenary Session. All of them enhanced an updated panorama of the current initiatives, difficulties and opportunities that Creative Cities of UNESCO are facing, allowing to draw some conclusions regarding the effectiveness of the Sustainable Urban Development goals’ implementation. From a report following the event’s exclusive personal attendance, and taking into account official documentation by UNESCO, we intend to analyse and discuss some of the main conclusions from the XI UCCN Annual Meeting.